2014
DOI: 10.1002/hbm.22553
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress modulates amygdala‐prefrontal functional connectivity: Implications for oxytocin effects

Abstract: Recent evidence suggests that early life stress (ELS) changes stress reactivity via reduced resting state functional connectivity (rs-FC) between amygdala and the prefrontal cortex. Oxytocin (OXT) modulates amygdala connectivity and attenuates responses to psychosocial stress, but its effect appears to be moderated by ELS. Here we first investigate the effect of ELS on amygdala-prefrontal rs-FC, and examine whether ELS-associated changes of rs-FC in this neural circuit predict its response to psychosocial stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
85
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 102 publications
10
85
3
2
Order By: Relevance
“…At a first glance, this seems inconsistent with previous findings that ELS is associated with decreased amygdala-prefrontal FC during resting state (Burghy et al, 2012;Fan et al, 2014;Herringa et al, 2013). However, it is important to emphasize that task-evoked FC changes reflect transient changes in brain network coupling in response to specific task demands.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…At a first glance, this seems inconsistent with previous findings that ELS is associated with decreased amygdala-prefrontal FC during resting state (Burghy et al, 2012;Fan et al, 2014;Herringa et al, 2013). However, it is important to emphasize that task-evoked FC changes reflect transient changes in brain network coupling in response to specific task demands.…”
Section: Discussioncontrasting
confidence: 82%
“…Task-evoked FC changes between amygdala and other limbic-prefrontal regions have been demonstrated during transient acute stress (Hermans et al, 2011;Vaisvaser et al, 2013;Veer et al, 2011). It has also been shown that ELS impacts structural connectivity and trait-like rs-FC within the limbic-prefrontal circuit (Burghy et al, 2012;Fan et al, 2014;Hart and Rubia, 2012;Herringa et al, 2013). Here we hypothesize that ELS influences stress-induced FC changes from amygdala to mPFC and hippocampus.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Finally, for all significant results, we additionally adjusted for sex, lifetime PTSD, duration between intranasal administration and scanning, and (for fMRI analyses only) experienced childhood trauma in separate models (Fan et al, 2014;Paloyelis et al, 2014;Rilling et al, 2014).…”
Section: Resultsmentioning
confidence: 99%